Testosterone and Vitamin D Deficiency as Risk Factors for Hip Fracture Elderly Male Patients: Time for Vitamin D and Testosterone Replacement (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: osteoporosis; fracture neck of femur; hip fracture; testosterone; bone mineral density; vitamin D; 25(OH)D; 1; 25(OH)#x2082; D secondary hyperparathyroidi